Knowledge gaps in reproductive and sexual health in girls and women with sickle cell disease. (7th July 2021) - Pecker, Lydia H.; Sharma, Deva; Nero, Alecia; Paidas, Michael J.; Ware, Russell E.; James, Andra H.; Smith‐Whitley, Kim
Summary: There is an immediate need to address long‐standing questions about the reproductive health of girls and women with sickle cell disease (SCD). There are many SCD‐related reproductive risks and uncertainties across girls' and women's reproductive life span, with particularly outstanding concerns about menstruation, contraception, fertility and pregnancy. Extant literature addressing women's reproductive health topics is mostly descriptive; there are few high‐quality interventional studies. In 2020, the Centers for Disease Control and Prevention and the Foundation for Women and Girls with Blood Disorders convened an expert panel to assess the knowledge gaps in women's reproductive health in SCD. The panel identified significant limitations to clinical care due to the need for research. The panel also identified prominent barriers to research and care. In this report, we frame these issues, providing a roadmap for investigators, funding agencies, and policy makers to advance care for girls and women with SCD.